2022
DOI: 10.3389/fimmu.2022.1021924
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids as inflammatory mediators and modulators of intestinal permeability

Abstract: Bile acids are critical for the digestion and absorption of lipids and fat-soluble vitamins; however, evidence continues to emerge supporting additional roles for bile acids as signaling molecules. After they are synthesized from cholesterol in the liver, primary bile acids are modified into secondary bile acids by gut flora contributing to a diverse pool and making the composition of bile acids highly sensitive to alterations in gut microbiota. Disturbances in bile acid homeostasis have been observed in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 128 publications
(201 reference statements)
0
14
0
Order By: Relevance
“…The conversion of host-derived primary bile acids into secondary bile acids by gut microbiota is another key mechanism for improving intestinal barrier function ( 47 ). With strong bile salt hydrolase activity, Coprococcus , Butyricicoccus , Ruminococcus, and Bacteroides play an essential role in secondary bile acid biotransformation ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of host-derived primary bile acids into secondary bile acids by gut microbiota is another key mechanism for improving intestinal barrier function ( 47 ). With strong bile salt hydrolase activity, Coprococcus , Butyricicoccus , Ruminococcus, and Bacteroides play an essential role in secondary bile acid biotransformation ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea, dehydration, and undernutrition are the most prominent symptoms in this group, and their severity mainly depends on the factors listed above ( Table 4 , and Figure 5 ) and especially on the location and extent of the removed intestinal segment. Thus, some functions of the ileum (e.g., bile salt and vitamin B12 absorption) are specific to this anatomical segment and cannot be supplied by the jejunum [ 59 , 60 , 61 , 62 , 63 ]. In addition, the ileum typically reabsorbs a large portion of the fluid secreted by the jejunum.…”
Section: Short Bowel Syndrome (Sbs)mentioning
confidence: 99%
“…Activation of these receptors plays an essential role in preserving the integrity of intestinal barrier, regulating immune homeostasis and alleviating IBD with considerable efficacy [82], which is widely proved in human and animal models. Golden et al showed that ursodeoxycholic acid protected against intestinal barrier breakdown in an acute rodent injury model through the activation of epidermal growth factor receptor and the upregulation of cyclooxygenase 2 [83].…”
Section: Basmentioning
confidence: 99%